Original paperWhat is the optimal cut-off point for low coronary artery calcium score assessed by computed tomography? Multi-Detector Computed Tomography ANIN Registry - Kaczmarska, Edyta; Kępka, Cezary; Dzielińska, Zofia; Pracoń, Radosław; Kryczka, Karolina; Petryka, Joanna; Pręgowski, Jerzy; Kruk, Mariusz; Demkow, Marcin (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Aim: This prospective study was conducted to evaluate the incidence and predictors of coronary artery disease (CAD) in relation to the low coronary artery calcium (CAC) score among patients with intermediate probability of CAD. Material and methods : A total of 1132 consecutive patients were included in the analysis (58.7 ±10.9 years, 46.7% males). Coronary computed tomography (CCT) angiography was performed in a multi-detector computed tomography scanner. Coronary artery calcium score was calculated by the Agatston method. Obstructive CAD was defined as the presence of coronary artery stenosis ≥ 50% on CCT angiography. Results : Coronary artery disease was diagnosed in nearly one-fourth of patients (n = 272, 24%). In the receiver operating characteristics (ROC) curve analysis a CAC score of 10 was used as an optimal cut-off point for discriminating obstructive CAD (sensiti-vity: 0.79, specificity: 0.75, p < 0.0001) whereas for a CAC score of 100 the sensitivity and specificity were 0.48 and 0.92, respectively. On multivariate analysis after adjustment for age, gender, hypertension, hyperlipidemia, creatinine levels, only in patients with CAC score ≤ 10 age (OR = 1.05, 95% CI: 1.02-1.08, p = 0.0005, OR = 1.05, 95% CI: 1.03-1.08, p < 0.0001) and male gender (OR = 3.45, 95% CI: 1.92-6.22, p < 0.0001), likewise in group with CAC score ≤ 100 age (OR = 1.05, 95% CI: 1.03-1.08, p < 0.0001) and male gender (OR = 3.31, 95% CI: 1.88-5.81, p < 0.0001) were independent predictors of obstructive CAD. Conclusions: The cut-off point of 10 for CAC score determined patients with CAD with the best sensitivity and specificity. Therefore, a total CAC score < 10 should be classified as “low”. In patients with a low CAC score obstructive high risk plaques prone to rupture are presented and are associated with increasing age and male gender.